2019
DOI: 10.1016/j.adro.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

MRI Radiomic Features Are Independently Associated With Overall Survival in Soft Tissue Sarcoma

Abstract: Purpose Soft tissue sarcomas (STS) represent a heterogeneous group of diseases, and selection of individualized treatments remains a challenge. The goal of this study was to determine whether radiomic features extracted from magnetic resonance (MR) images are independently associated with overall survival (OS) in STS. Methods and Materials This study analyzed 2 independent cohorts of adult patients with stage II-III STS treated at center 1 (N = 165) and center 2 (N = 61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 38 publications
2
47
0
Order By: Relevance
“…Our results also deepened that intra-tumoral heterogeneous SIs on T2-WI is predictive of MFS in a quantitative manner and other studies have also correlated this parameter with overall and/or metastatic-relapse free survivals in STS patients with relatively close and similar performances to ours 6,7,20 . Indeed, Peeken et al used an equivalent of IHTstd and applied ComBat to correct for multicenter effect.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results also deepened that intra-tumoral heterogeneous SIs on T2-WI is predictive of MFS in a quantitative manner and other studies have also correlated this parameter with overall and/or metastatic-relapse free survivals in STS patients with relatively close and similar performances to ours 6,7,20 . Indeed, Peeken et al used an equivalent of IHTstd and applied ComBat to correct for multicenter effect.…”
Section: Discussionsupporting
confidence: 83%
“…In this case, lowering these performances with a particular IHT would mean that this IHT caused noise and inappropriate deviation in the data. However, as already stated, prior studies converged towards same results regarding the relationship between MRI-based radiomics features, heterogeneity on T2-WI and outcomes of sarcoma patients 6,7,20,35 . Alternative study designs could have been proposed in the absence of such relationship, (i) either by using a phantom made of compartments with various degrees of heterogeneity, (ii) or by using MRIs of healthy volunteers covering organs with different textures and investigating which IHT enables the best radiomics-based classification of these organs (by analogy with the study by Orlhac et al) 19 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…It should be kept in mind that considerable overlap between benign and malignant lesions has been found with all of these techniques. Radiomic analysis of MR images has been shown to have some prognostic value in soft tissue sarcoma but is not yet a mature technique [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Spraker et al [20] found that radiomics features alone or combined with age and grade were respectively independent predictors of over survival, and the latter achieved best performance. Peeken et al [37] demonstrated that the radiomics model based on T1FSGd MRI sequences showed signi cant patient strati cation performance for overall survival, and improved prognostic performance was found with the combination of a T2FS radiomics model with the AJCC system.…”
Section: Discussionmentioning
confidence: 99%